Review of Change and Stability in Thesis and Dissertation Writing: The Evolution of an Academic Genre - Lestari, Febriana; Hakim, Angela (Journal of Academic Writing, 2025)
This is a book review of Change and Stability in Thesis and Dissertation Writing: The Evolution of an Academic Genre by Paltridge and Starfield (2024).